E-learning in Higher Education in Management: Enhancing Students’ Learning Outcomes and Satisfaction - Timilsina, Sambed; Thapa, Sagar; Pandey, Rohit (SADGAMAYA, 2025)
Modern management is supported and driven by advanced technology and its efficient use has positively evidenced to have contributed on student’s academic performance. This study examines the relationship and their contribution between e-learning and student performance in university level management education. A total 298 responses from the students of Bachelor and Master level of Kathmandu Metropolis were collected from survey and interview through structured questionnaire and analyzed relying on descriptive statistics, Pearson correlation analysis, and regression analysis to analyze the relationship between variables.The revealed results exhibited different e-learning tools effective in varied learning domains and insights. Most students were found gratified with the digital library for better performance among other tools. E-learning tools have a statistically significant effect on students' performance and these tools are a part of the e-learning ecosystem as a whole. The study supports that the technologies are instrumental in management education and integrating these variables in the educational diaspora significantly enhances students’ learning outcomes and satisfaction.